2010
DOI: 10.1111/j.1754-4505.2010.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental students’ perceived comfort and future willingness to treat underserved populations: surveys prior to and immediately after extramural experiences

Abstract: The purpose of this study was to compare the perceived change in comfort level and future willingness of senior dental students toward treating 12 different groups of traditionally underserved populations. Written surveys of senior dental students were conducted prior to and after completing extramural clinical rotations. A Likert-type scale was used to assess student comfort, whereas future willingness to treat these populations was dichotomous. Over a 13-year period (1992–2004), 560 students completed both s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 33 publications
(41 reference statements)
8
46
0
Order By: Relevance
“…Other studies demonstrated the same results for both working professionals and students, who demonstrate fear and negative tendencies toward HIV+ patients, as well as occasional discrimination [3][4][5][8][9][10][11][14][15][17][18]20 . What attracts particular attention in the findings of this study is the fact that students in semesters that have had little contact with the dental clinic, showed less apprehensive or fearful attitudes regarding the treatment of infected patients compared to students in more advanced semesters, of whom greater psychological preparation would be expected due to their greater practical experience.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Other studies demonstrated the same results for both working professionals and students, who demonstrate fear and negative tendencies toward HIV+ patients, as well as occasional discrimination [3][4][5][8][9][10][11][14][15][17][18]20 . What attracts particular attention in the findings of this study is the fact that students in semesters that have had little contact with the dental clinic, showed less apprehensive or fearful attitudes regarding the treatment of infected patients compared to students in more advanced semesters, of whom greater psychological preparation would be expected due to their greater practical experience.…”
Section: Discussionsupporting
confidence: 51%
“…What attracts particular attention in the findings of this study is the fact that students in semesters that have had little contact with the dental clinic, showed less apprehensive or fearful attitudes regarding the treatment of infected patients compared to students in more advanced semesters, of whom greater psychological preparation would be expected due to their greater practical experience. This same fact is reported in some studies 4,17 but differs from others 18 . The majority would treat patients infected with AIDS, however almost all of the students agreed that there should be some kind of specialized course on theoretical and practical knowledge regarding care of HIV+ patients.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…[28][29][30] However, the methodology used in those studies was not directly comparable to ours: their programs compared perceptions from current dental students or graduates who participated in two diferent types of programs (traditional curriculum versus community-based rotations) and assessed willingness to treat underserved populations. [28][29][30] However, the methodology used in those studies was not directly comparable to ours: their programs compared perceptions from current dental students or graduates who participated in two diferent types of programs (traditional curriculum versus community-based rotations) and assessed willingness to treat underserved populations.…”
Section: Post-rotation Attitudes About Community-based Dental Educamentioning
confidence: 99%
“…10,11 Data have shown that CBDE improves dental student competence, productivity, and conidence as well as exposes students to practice opportunities in underserved settings. [28][29][30][31][32] Further, one study reported that students' intended practice choice did not always accurately predict subsequent behavior. Some studies have shown a measurable efect of CBDE on practice plans and awareness or intent to care for vulnerable or underserved populations.…”
mentioning
confidence: 99%